A typological analysis of metaphor, proposed by George Lakoff and Mark Johnson, in the poems Bodas and Eclipse, in Consejero del lobo (1965), by the Peruvian poet Rodolfo Hinostroza - Delgado del Águila, Jesús Miguel (2019)
In the following article, I offer a literary analysis of two poems from Consejero del lobo (1965), by the Peruvian writer Rodolfo Hinostroza, with the aim of applying the concepts developed by George Lakoff and Mark Johnson (and interpreted subsequently by the critic Camilo Fernandez Cozman), to the typology of metaphors, addressing orientational, ontological and structural aspects emerging from the process of abstraction and identification of macro notions (through mega-metaphors) and micro signifiers (through specific metaphors). In addition, I will address the functions of other elements that intervene in this study, such as the identification of interlocutors, the worldview proposed by the poetic self, and interdiscursivity. The aim of this study is to establish theoretical guidelines to enable lyrical interpretation of the rhetorical figures derived from the aforementioned classification.